Spacer cation alloying in Ruddlesden-Popper perovskites for efficient red light-emitting diodes with precisely tunable wavelengths - Qing, Jian (2021)
Perovskite light-emitting diodes (PeLEDs) have recently shown significant progress with external quantum efficiencies (EQEs) exceeding 20%. However, PeLEDs with pure-red (620-660 nm) light emission, an essential part for full-color displays, remain a great challenge. Herein, a general approach of spacer cation alloying is employed in Ruddlesden-Popper perovskites (RPPs) for efficient red PeLEDs with precisely tunable wavelengths. By simply tuning the alloying ratio of dual spacer cations, the thickness distribution of quantum wells in the RPP films can be precisely modulated without deteriorating their charge-transport ability and energy funneling processes. Consequently, efficient PeLEDs with tunable emissions between pure red (626 nm) and deep red (671 nm) are achieved with peak EQEs up to 11.5%, representing the highest values among RPP-based pure-red PeLEDs. This work opens a new route for color tuning, which will spur future developments of pure-red or even pure-blue PeLEDs with high performance.